Opening Up the In-House:A Model for Collaborative Holistic Services and Education in Law School Clinical Programs - Melina A. Healey (Washington University Journal of Law and Policy, 2024)
Individual in-house clinics too commonly operate autonomously behind separate walls. These barriers impair the meaningful holistic representation of clients and the educational opportunities of clinic students. This article provides an argument and framework for opening the doors between clinics to enrich clinic student education and enhance client representation. Part I identifies the benefits of holistic inter-clinic collaboration for both clinic students and the clients they serve. Part II shares a model for how to integrate education and client service across practice areas of clinical programs. A forthcoming article, published separately, will further describe how clinical programs can be improved by removing silos in evaluation and creating unified programmatic-level clinical student and course assessment tools, which can in turn also illustrate the essential value of clinic to legal education.
Keywords: LegalEducation; ClinicalCollaboration; HolisticRepresentation; InterClinicIntegration; StudentLearningEnhancement